Road safety status during COVID-19 pandemic: exploring public and road safety expert's opinions. Issue 2 (17th May 2022) - Alhajyaseen, Wael K. M.; Almukdad, Abdulkarim; Hussain, Qinaat; Almallah, Mustafa; Al Malki, Mohammed Abdullah; Singaravelu, Jayaseelan; Zammataro, Susanna
Abstract: The main objective of this study is to investigate the status of traffic safety and the public perception of traffic safety during the during COVID-19 pandemic. Three different data sets are used in this study: road crash and traffic violation data from Qatar, and two separate questionnaire surveys (from general public and road safety experts). Results showed that during COVID-19 period, the total number of crashes in Qatar significantly reduced during the pandemic compared with the previous 5 years. However, the rates of serious and fatal injuries significantly increased. Regarding the general public perceptions, more than 80% reported that roads became safer while driving behaviours improved during the pandemic. On the other hand, more than 50% of the experts disagreed that roads became safer, 55% disagreed that driving behaviours improved and 70% agreed that less attention from governments was directed toward road safety during the pandemic. The findings from this study could help policy makers to understand the road safety status during the pandemic to make appropriate adjustments in the traffic laws and regulations on a temporary basis. This could help in reducing crash-related injuries and as a result reduce pressure on health and other emergency services.